Enterprise Risk Disclosed in Initial Public Offering in Brazil - Cunha, Paulo Roberto da; Silva, Júlio Orestes da; Fernandes, Francisco Carlos (Review of Business Management, 2011)
The current legislation in Brazil requires that companies wishing to raise funds in capital markets through issuance of shares shall prepare a prospectus for Initial Public Offering (IPO) in which they inform, among other things, all risks that may affect the business. The aim of this paper is to investigate the level of disclosure of business risks reported in these prospectuses. The methodological design was a descriptive qualitative approach. The object of analysis consisted of the final prospectus for IPO listed in the Brazilian Securities Commission (CVM) in 2008. The sample consisted of 10 companies from various segments. We have adopted a criterion score by which it was found that the average percentage score achieved was 59% of disclosure. We have also defined indicators of the level of disclosure by risk category and by company. Within these categories, this percentage ranged from 42% of the category “risks of issuing” up to 85% in category “risks related to the shareholder”. As for the scores of companies, the lowest score was obtained by Le Lis Blanc, 51%, while the Vale do Rio Doce has obtained the highest score, 66% of the total possible. In conclusion, it was found that the level of disclosure of risks in stock offering prospectus is not yet satisfactory. Possible causes for this phenomenon are analyzed. Key words: Risk. Disclosure. IPO. Initial public offering.